Kinship Terms Used By Younger Speakers Of Lahat Language: A Case Study On Smp Negeri 1 Merapi Timur - Sulastry, Heny; Salamah, Salamah; S, Zulkarnain (Yayasan Darussalam Bengkulu, 2021)
Kinship is important in the organization of social life and every language has its own kinship terminology. And this study deals with the kinship terms used in Lahat Language. The objective of the study were: (1) to find out the kinship terms in Lahat language used by the students of SMP Negeri 1 Merapi Timur as the younger speakers, and (2) to find out the differences between the kinship terms used by the students as the younger speakers of Lahat language and the kinship terms used by the old speakers of Lahat language. The sample was students of SMP Negeri 1 Merapi Timur and 150 other informant of the old speakers of Lahat language. A descriptive method was used in this study. The data were obtained by means of interview and questionnaire. The data were analyzed by using descriptive qualitative method and using feature analysis. Interpretation of the result of the study describes kinship terms in Lahat language which are divided into: (1) Kinship terms in family, and (2) Kinship terms in society. Kinship terms in family are divided into: (1) Kinship terms in family based on blood relation, (2) kinship terms in family based on marriage relation, and (3) Kinship terms in family in special condition. Kinship terms in society are divided into: (1) Kinship terms in formal situation, and (2) Kinship terms in informal situation. There are many different terms used by young speakers and by old speakers which have been found in this study, such as terms for father, mother, parents-in-law, etc. for instance, to refer to father, younger speakers use baq or bapang and old speakers use bapaq, to refer to mother, younger speakers use umaq or maq and old speakers use endong, and to refer to parents-in-law, younger speakers use mentue and old speakers use pengiran. Hopefully this study will enlarge the knowledge about sociolinguistic and the study can be used by the younger speakers of lahat language to know the kinship terms in their mother tongue.